RIVER INFORMATION SERVICES AND THEIR APPICATION IN THE CONDITIONS OF THE DANUBE NAVIGATION (Perner's Contacts, 2010)
Analysis of the causes and reasons for the creation of River Information Services (RIS). Function arrangement of the system of River Information Services with the application of telematic technologies. The characteristic of the main telematic parts of the system. The status quo of the installation and application of the system of River Information Services in Slovakia.
Keywords: telematics; water transport; river information services; electronic chart